2019
DOI: 10.1158/1535-7163.mct-18-1068
|View full text |Cite
|
Sign up to set email alerts
|

HDAC3 Inhibition Upregulates PD-L1 Expression in B-Cell Lymphomas and Augments the Efficacy of Anti–PD-L1 Therapy

Abstract: Programmed cell-death protein 1 (PD-1) and programmed death-ligand 1 (PD-L1) pathway blockade is a promising therapy for the treatment of advanced cancers, including B-cell lymphoma. The clinical response to PD-1/ PD-L1 immunotherapy correlates with PD-L1 levels on tumor cells and other cells in the tumor microenvironment. Hence, it is important to understand the molecular mechanisms that regulate PD-L1 expression. Here, we report that histone deacetylase 3 (HDAC3) is a crucial repressor of PD-L1 transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 50 publications
4
67
0
Order By: Relevance
“…We showed that OKI-179 also upregulated PD-L1 expression in B-cell lymphomas but not in primary B cells (Wang et al, 2019). Notably, OKI-179 exhibits potent inhibitory activities on HDAC 1, 2 and 3 (Wang et al, 2019), consistent with the notion that HDAC3 is a crucial repressor of PD-L1 transcription (Deng et al, 2019).…”
Section: Immune Modulation Of B-cell Lymphomas By Hdac Inhibitorssupporting
confidence: 78%
See 3 more Smart Citations
“…We showed that OKI-179 also upregulated PD-L1 expression in B-cell lymphomas but not in primary B cells (Wang et al, 2019). Notably, OKI-179 exhibits potent inhibitory activities on HDAC 1, 2 and 3 (Wang et al, 2019), consistent with the notion that HDAC3 is a crucial repressor of PD-L1 transcription (Deng et al, 2019).…”
Section: Immune Modulation Of B-cell Lymphomas By Hdac Inhibitorssupporting
confidence: 78%
“…Pan-HDAC inhibitors, such as vorinostat, TSA and panobinostat, induce PD-L1 expression in B-cell lymphomas (Deng et al, 2019). Selective HDAC3 inhibitors (e.g., RGFP966) also upregulated PD-L1 expression because HDAC3 was shown to repress PD-L1 transcription in B-cell lymphomas (Deng et al, 2019). We showed that OKI-179 also upregulated PD-L1 expression in B-cell lymphomas but not in primary B cells (Wang et al, 2019).…”
Section: Immune Modulation Of B-cell Lymphomas By Hdac Inhibitorsmentioning
confidence: 78%
See 2 more Smart Citations
“…In 32 types of cancers analyzed, we only detected positive associations between PD-L1 and macrophages or T cell lineage markers in 21, showing that, in the other 11 types of cancers analyzed, major factors contributing to tumor PD-L1 induction were unrelated to the immune landscapes. In fact, besides being induced by immune landscapes, tumor PD-L1 might be regulated by many other biological processes, including chromosomal rearrangements, copy number alterations, oncogenic pathway dysregulation, and epigenetic modulation (47)(48)(49)(50). In addition, although our current work focuses on the prognostic value and the immune landscapes of PD-L1 + cancer cells, PD-L1 + host cells, particularly macrophages and dendritic cells, also play very important roles in promoting cancer progression (16)(17)(18).…”
Section: Pd-l1 Mirrors Multiple Immune Signatures In Human Cancersmentioning
confidence: 97%